The Academic Preparation of Idaho Science Teachers Based on School District Size - Michael W. Heikkinen (Journal of Research in Rural Education, 1987)
The certification records of 435 of the 632 teachers who taught science in Idaho during the 1983-84school year were examined. Data recorded included subject endorsed to teach, highest degree held, and sciencecredits taken at the collegelevel. The academic preparation of Idaho science teachers was examined by subject taught and size of school district. Significant differences were found for the following when analyzed by school district size. Physiology, earth science, and chemistry I teachers in the largest school districts had more credits in the subjects they taught. Earth science and chemistry I teachers in the largest districts had a higher frequency of a major in the subject taught and those teachers in the smallest school districts had a higher frequency of having neither a major or minor in the subject taught. A larger percentage of physiology, earth science, and chemistry I teachers in the largest school districts had endorsements to teach the subjects they were assigned. Scienceteachers in the smaller school districts had significantly more different subjects to prepare to teach.